Speculative Attacks with Multiple Sources of Public Information - Camille Cornand; Frank Heinemann (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
We propose a speculative attack model in which agents receive multiple public signals. It is characterised by its focus on an informational structure which sets free from the strict separation between public information and private information. Diverse pieces of public information can be taken into account differently by players and are likely to lead to different appreciations ex post. This process defines players' private value. The main result is to show that equilibrium uniqueness depends on two conditions: (i) signals are sufficiently dispersed (ii) private beliefs about the relative precision of these signals sufficiently differ. We derive economic policy implications of such a result.
urn:nbn:de:bvb:19-epub-13394-2
Keywords: F31; D82; 330; Speculative attack; Private value game; Multiple equilibria; Public and private information